JURIDICAL ANALYSIS OF WANPRESTASI IN THE PERSPECTIVE OF AGREEMENT LAW IN INDONESIA - Amaria Irfani; Imroatul Maulida; Rodotul Fitriya; Rohmatul Mawaddah; Siti Asimatunisa; Siti Liza Azizah (Jurnal Recoms, 2025)
The purpose of this study is to provide readers with a deeper understanding of legal findings from the perspective of Islamic economic law. This research uses a qualitative method, which is a type of library research that involves collecting data or documents related to legal findings from the perspective of Islamic economic law. The development and implementation of Sharia law in financial institutions will have a significant impact on social and environmental performance. Therefore, the most important reform of Islamic Sharia law is carried out through legal processes and religious court decisions after the ijtihad of judges. In addition to research conducted by several universities in Indonesia, they are also involved in research on Islamic law, especially Islamic economics. from this research, there are several aspects of legal modifiers, there are also developments and extensions of Islamic economic law that have a major influence on the activities of society and its environment.